1150 Mixie, a tool to improve assessment of chemical risk in case of multiple exposure. (24th April 2018) - Coates, L; Bertrand, N; Binet, S; Campo, P; Clerc, F; La Rocca, B; Pillière, F
Abstract : Introduction: Multiple exposure to chemicals is a common situation in workplaces. However, most methods used to evaluate chemical risk do not consider the potential effects of mixtures. The aim is to present a tool helping to evaluate chemical risk in case of multiple exposure. Methods: MiXie is a web tool (http://www.inrs-mixie.fr/http://www.inrs-mixie.fr/) developed in Quebec in 1997 and adapted to the French context by the French National Research and Safety Institute for the prevention of occupational accidents and diseases (INRS). It helps industrial hygienists to assess the potential risk of multi-exposure. Additivity of effects is the basic assumption. Results: Whenever measurements of atmospheric concentrations are provided, MiXie calculates the exposure index of the mixture (i.e. the sum of the ratios between each concentration measured and its occupational exposure limit value x 100). If this index exceeds 100%, MiXie signals that there is a potential risk for certain organs, even though each limit value is respected. When measurements of atmospheric concentrations are not provided, MiXie highlights the common effects classes of the substances present and warns about a potential risk of additive effects. If the mixture contains a substance belonging to the 'cancer' or 'sensitizer' effect class, additivity does not apply and MiXie warns the industrial hygienist regardless of the concentration measured. Conclusion: The MiXie database helps to identify potential risk situations related to multi-exposure to chemicals. Such situations may go unnoticed with a monosubstance approach. But MiXie users should be aware of its limits: additivity does not apply to all situations, the number of substances is restricted (130), etc. Experts are working to improve the tool by increasing the number of substances, making it more user-friendly, etc.